Effect of the Multipole Pairing and Particle-Hole Fields in the Particle-Vibration Coupling of 209Pb. II. The 207Pb(t,p)209Pb Reaction at 20 MeV - Flynn, E. R. (1971)
Fil: Flynn, E. R. Los Alamos Scientific Laboratory; Estados Unidos